PERSONALITY TRAITS AND ASSOCIATED FACTORS AMONG UNDERGRADUATE MEDICAL STUDENTS AT DAI NAM UNIVERSITY, 2024–2025 (Tạp chí Y học Cộng đồng, 2026)
Objective: To describe Big Five personality traits and identify associated factors among undergraduate medical students at Dai Nam University during the 2024–2025 academic year.Subject and method: A cross-sectional study was conducted among 360 undergraduate medical students. Data were collected using a structured self-administered questionnaire, including general characteristics and a 21-item Big Five–based personality scale. Five personality domains were assessed: extraversion, agreeableness, conscientiousness, neuroticism, and openness to experience. Descriptive statistics and multivariable linear regression were used for data analysis.Results: Among 360 students, males accounted for 59.72% and females for 40.28%. The highest mean personality score was observed for openness to experience (3.53 ± 0.64), followed by agreeableness (3.40 ± 0.70), conscientiousness (3.38 ± 0.59), neuroticism (3.20 ± 0.67), and extraversion (2.98 ± 0.61). Female students had significantly higher agreeableness scores than male students (Coef. = 0.239; 95% CI: 0.090–0.389; p < 0.01). Compared with fifth-year students, first-year students had higher agreeableness and neuroticism scores, second-year students had higher neuroticism and openness to experience scores, and third-year students had higher conscientiousness scores. Academic performance was significantly associated with conscientiousness and openness to experience. Students without a part-time job had lower extraversion scores than those with a health-related part-time job.Conclusion: Medical students showed moderate levels of all Big Five personality traits, with openness to experience being the most prominent and extraversion the lowest. Gender, year of study, academic performance, and part-time employment status were associated with specific personality traits.
Keywords: Big Five personality traits; medical students; undergraduate students; academic performance; associated factors.